Community-based intervention via WeChat official account to improve parental health literacy among primary caregivers of children aged 0 to 3 years: Protocol for a cluster randomized controlled trial - Li, Yun; Xiao, Qiu-Li; Li, Mu; Zhang, Yue; Chen, Min; Jiang, Chun-Hua; Kang, Shu-Rong; Zhang, Ying; Huang, Jun; Jiang, Hong (Frontiers in Public Health, 2023)
Background Parental health literacy is an important determinant of children's health, especially during the critical window of early development in the first 3 years. As the information communication technology develops, health education via social media is widely used to deliver health information. However, few studies have explored the effect of intervention via social media on parental health literacy. Objective This study aims to determine whether a WeChat official account-based health intervention can improve parental health literacy of primary caregivers of children aged 0 to 3 years in Minhang District, Shanghai, China. Methods The cluster randomized controlled trial includes all 13 community health centers (CHCs) in Minhang District, Shanghai. We take each CHCs as a cluster in the randomization. The CHCs are randomly allocated to the intervention or the control group through random sequence generation. Ninety primary caregivers of children aged 0 to 2 years will be recruited from each CHC, 1170 in total. Caregivers in the intervention group will be provided with a series of video clips and online reading material links on scientific parenting via a WeChat account. Caregivers in the control group will receive printed educational materials with similar contents to the intervention group. All the participants will access routine child health care and be followed up for 9 months. Online assessment of health literacy will be conducted for both groups before and after the intervention. The primary outcome is the change in the total scores of parental health literacy using a validated instrument. The data of secondary outcomes, such as exclusive breastfeeding in the first 6 months, anthropometric measurements, and disease conditions, will be extracted from routine health care records. Generalized linear mixed model (GLMM) will be used for data analyses. Discussion Compared with traditional health education, health intervention via WeChat official account could be a feasible and effective solution to improve parental health literacy. Trial registration This trial is registered with the Chinese Clinical Trial Registry (ChiCTR): (#ChiCTR2000031711) on April 07, 2020.